Forschung in der Spannung zwischen Erheben des Status quo und pädagogischer Realisierung einer Vision ... – aufgezeigt am Beispiel Lebens-, Wert- und Sinnorientierung Jugendlicher im Hinblick auf die Verwirklichung von Inklusion - Franz Feiner (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2014)
In the article, the current KPH Graz Jugendwertestudie is displayed: • In the historical development process, as a research from the „Firmungsstu- die” to the intercultural and inter-religious Values Study • Classified in an interdisciplinary question, namely the sense and value of life • Tolerance was established as a fundamental value regarding the study • The “more” of “tolerance”, namely the “acceptance” from the religions, for example the Islam in terms of the “Projekt Weltethos” (project world ethos) (H. Küng), where all religions shall use their ethical potential for the world’s future. • The learning of empathy and solidarity is viewed in an European dimension and is based on the vision of a worldwide inclusive society and a concretization of “steps into the future” is indicated too. The current European research project ETHOS has investigated the needs of all stakeholders (children, students, teachers, parents) and has developed holistic pedagogical-didactic materials for the age group of 3 to 15. • The inspiring principles of the Catholic Social Doctrine as a major impetus towards a “planetarischen Bewusstseins“ (planetary consciousness) (L. Boff) are going to be included, where we see ourselves as “citizens of the world” and can understand and help to form a new, more inclusive society.